MEMBENTUK SUMBER DAYA MANUSIA YANG BERDAYA SAING TINGGI MELALUI PENDIDIKAN KARAKTER BERSIFAT RELIGIUS DI ERA DISRUPTIF - Dewi, Nabila Puspa; Nadina, Gina; Rachman, Ichsan Fauzi (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
This disruptive era demands changes in terms of education. One of them is that we must have highly competitive human resources. Therefore, character education is one of the efforts to improve human resources in Indonesia. This is done deliberately in order to shape a person to understand and act in accordance with applicable ethical values. The character in question is a religious attitude. The research method used in this research is literature review(literature review). Good character will encourage good attitudes in our daily behavior. Religious education becomes a means of transformation in various aspects, including the religious aspect (cognitive aspect), the moral value aspect to form attitudes (affective aspect) and the behavioral control aspect (psychomotor aspect). Thus, a complete personality is created. Character education must be integrated into a curriculum so that character education can be the right way to implement it character building for students as the young generation who have high knowledge and are equipped with faith and devotion to God Almighty, have noble character in a disruptive era where technology, innovation and social change significantly disrupt or change the way of life of humans as a whole.